Shared immunotherapeutic approaches in HIV and hepatitis B virus: combine and conquer. Issue 3 (May 2020) - Maini, Mala K.; Peppa, Dimitra
Abstract : Purpose of review: The aim of this study was to identify similarities, differences and lessons to be shared from recent progress in HIV and hepatitis B virus (HBV) immunotherapeutic approaches. Recent findings: Immune dysregulation is a hallmark of both HIV and HBV infection, which have shared routes of transmission, with approximately 10% of HIV-positive patients worldwide being coinfected with HBV. Immune modulation therapies to orchestrate effective innate and adaptive immune responses are currently being sought as potential strategies towards a functional cure in both HIV and HBV infection. These are based on activating immunological mechanisms that would allow durable control by triggering innate immunity, reviving exhausted endogenous responses and/or generating new immune responses. Recent technological advances and increased appreciation of humoral responses in the control of HIV have generated renewed enthusiasm in the cure field. Summary: For both HIV and HBV infection, a primary consideration with immunomodulatory therapies continues to be a balance between generating highly effective immune responses and mitigating any significant toxicity. A large arsenal of new approaches and ongoing research offer the opportunity to define the pathways that underpin chronic infection and move closer to a functional cure.